Intercensal and Postcensal Estimation of Population Size for Small Geographic Areas in the United States - Wang, Yan; Zhang, Xingyou; Lu, Hua; Matthews, Kevin A; Greenlund, Kurt J (International Journal of Population Data Science, 2020)
Introduction Population estimation techniques are often used to provide updated data for a current year. However,estimates for small geographic units, such as census tracts in the United States, are typically notavailable. Yet there are growing demands from local policy making, program planning and evaluationpractitioners for such data because small area population estimates are more useful than those forlarger geographic areas. Objectives To estimate the population sizes at the census block level by subgroups (age, sex, and race/ethnicity)so that the population data can be aggregated up to any target small geographic areas. Methods We estimated the population sizes by subgroups at the census block level using an intercensal ap-proach for years between 2000 and 2010 and a postcensal approach for the years following the2010 decennial census (2011-2017). Then we aggregated the data to the county level (intercensalapproach) and incorporated place level (postcensal approach) and compared our estimates to corre-sponding US Census Bureau (the Census) estimates. Results Overall, our intercensal estimates were close to the Census’ population estimates at the countylevel for the years 2000-2010; yet there were substantive errors in counties where population sizesexperienced sudden changes. Our postcensal estimates were also close to the Census’ populationestimates at the incorporated place level for years closer to the 2010 decennial census. Conclusions The approaches presented here can be used to estimate population sizes for any small geographicareas based on census blocks. The advantages and disadvantages of their application in public healthpractice should be considered.